x(x-5)(x+5)-(x+2)(x^2-2x+4)=3

Question

x(x-5)(x+5)-(x+2)(x^2-2x+4)=3

in progress 0
Cherry 1 year 2020-10-31T01:36:15+00:00 2 Answers 151 views 0

Answers ( )

    0
    2020-10-31T01:37:34+00:00

    x(x-5)(x+5)-(x+2)(x^2-2x+4)=3

    ⇔x(x^2-25)-(x^3+2^3)=3

    ⇔x^3-25x-x^3-8=3

    ⇔-25x=11

    ⇔x=-11/25

                     

                             -Chúc bạn học tốt-

                                           -Thiênlinh2831-

    0
    2020-10-31T01:38:13+00:00

    Đáp án:

     

    Giải thích các bước giải:

     x(x – 5)(x + 5) – (x + 2)(x^2 – 2x + 4) = 3

    => x^3 – 25x – (x^3 + 2^3) = 3

    => x^3 – 25x – (x^3  + 8) = 3

    => x^3 – 25x – x^3 – 8 = 3

    => -25x = 11

    => x = -11/25

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )